A systematic review of SF-6D health state valuation studies. (31st December 2023) - Wang, Liang; Poder, Thomas G.
Abstract: Background: The short-form 6-dimension (SF-6D) is a preference-based measure designed to calculate quality-adjusted life-year (QALY). Preference-based measures are standardized multidimensional health state classifications with preference or utility weights elicited from a sample of the population. There is a concern that valuations may differ between countries because of differences in culture, thus invalidating the use of values obtained from one country to another. Objective: To conduct a systematic review of elicitation methods and modeling strategies in SF-6D studies and to present a general comparison of dimensions' ordering among different countries. Methods: We performed a systematic review of studies that developed value sets for the SF-6D. The data search was conducted in PubMed, ScienceDirect, Embase, and Scopus up to 8 September 2022. Quality of studies was assessed with the CREATE checklist. Methodological differences were identified, and the dimensions' ordering of the selected studies was analyzed by cultural and economic factors. Results: From a total of 1369 entries, 31 articles were selected. This corresponded to 12 different countries and regions and 17 different surveys. Most studies used the standard gamble method to elicit health state preferences. Anglo-Saxon countries gave more importance to pain, while other countries have physical functioning as the highest dimension. As the economic level increases, people care less about physical functioning but more about pain and mental health. Conclusions: Value sets for the SF-6D are different from one country to another and there is a need to develop value sets for more countries to consider cultural and economic differences.